2017
DOI: 10.1007/s41230-017-7178-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hot isostatic pressing temperature on casting shrinkage densification and microstructure of Ti6Al4V alloy

Abstract: T i6Al4V alloy has the properties of small density, high strength and good corrosion resistance. However, Ti6Al4V alloy castings are prone to shrinkage porosity due to its poor fluidity, leading to the poor performance of components. The defects must be reduced to a minimum level, especially in the field of aerospace and other high-quality-requirement industry. Hot isostatic pressing (HIP) has been proved to be a very effective way to eliminate or reduce shrinkage. A workpiece is heated and put under uniform p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The fraction of recrystallized grains around the pore increased significantly, and the recrystallized grains obviously grew up with the increase in HIP dwell time compared with HIP-2. When compared with shrinkage cavities and shrinkage porosities [14], the gas pores cannot be completely closed after a standard HIP cycle (HIP-3).…”
Section: Kinetics Of Pore Closure During Hipmentioning
confidence: 99%
See 1 more Smart Citation
“…The fraction of recrystallized grains around the pore increased significantly, and the recrystallized grains obviously grew up with the increase in HIP dwell time compared with HIP-2. When compared with shrinkage cavities and shrinkage porosities [14], the gas pores cannot be completely closed after a standard HIP cycle (HIP-3).…”
Section: Kinetics Of Pore Closure During Hipmentioning
confidence: 99%
“…To our knowledge, there are only a few publications focusing on the simulation of the void closure during HIP. Xu et al [14] investigated the effect of different HIP temperatures on void closure and found that the void can be closed when the HIP temperature is above 920 • C. Epishin et al [13] studied the pore annihilation in a single-crystal nickel-based superalloy during HIP by experiment and simulation. Two mechanisms for pore closure were revealed: the void was closed by plastic deformation and diffusion.…”
Section: Introductionmentioning
confidence: 99%
“…Hot isostatic pressing (HIP) can compact the internal defects through high pressure, thus improving the overall mechanical properties of the components. Xu et al [16] studied the effects of HIP temperature on as-cast TC4, the results showed that the shrinkage was reduced as the HIP temperature increased, and even completely closed above 920 ºC. Jiang et al [17] found that after HIP, the porosity defects in direct laser deposition Ti60 alloy disappeared, and the elongation increased from 6.5% to 12.0%, while maintaining tensile strength over 1,000 MPa.…”
Section: Introductionmentioning
confidence: 99%